Circular RNA-CDR1as is involved in lung injury induced by long-term formaldehyde inhalation. (6th December 2021) - Liu, Qiu-Ping; Ge, Pan; Wang, Qian-Nan; Zhang, Shu-Yu; Yang, Yan-Qi; Lv, Mo-Qi; Lu, Ye; Li, Man-Xiang; Zhou, Dang-Xia
Abstract: Objective: Formaldehyde (FA) is known to induce lung injury, but the underlying molecular mechanism remains largely unclear. CDR1as is an important member of the circular RNAs (circRNAs) family and functions as miRNA sponges with gene-regulatory potential. Our earlier circRNA microarray data showed CDR1as was highly expressed in lung tissue exposed to FA. However, the mechanism of circRNA-CDR1as mediates the FA-exposed lung injury is still unclear. This study aimed to explore the role of CDR1as in lung injury. Materials and methods: In this study, FA was inhaled at doses of 0.5, 2.46, and 5 mg/m3, respectively. After exposure 8 weeks, lung histopathological examination, lung injury score, and IL-1β in bronchoalveolar lavage fluid (BALF) were determined. The expressions of CDR1as, rno-miR-7b and Atg7 were detected and the potential interaction of circRNA/miRNA/mRNA was predicted by bioinformatics analysis, including drawing circRNA/miRNA/mRNA interaction network, GO and KEGG analysis. Results: Our results indicated FA inhalation upregulated the expression of CDR1as in lung tissues in a dose-dependent manner while the expression of rno-miR-7b decreased and Atg7 increased. Moreover, the alteration of CDR1as was positively correlated with lung injury. Discussion and conclusions: CircRNA/miRNA/mRNA prediction further explained the possible effect mechanisms of CDR1as. These data implicated that CDR1as might be a critical regulator involved in lung injury induced by FA.